Application of FRAC (Financial Ratio Analysis Card) Media to Improve Learning Activities and Learning Outcomes of Students of SMK Tamansiswa 1 Jakarta in Accounting Subjects (Wiyatamandala, 2025)
This study aims to improve students' learning activities and outcomes through the implementation of the FRAC Smart Card (Financial Ratio Analysis Card) in Accounting subjects at SMK Tamansiswa 1 Jakarta. The research employed a Classroom Action Research (CAR) design, conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 32 twelfth-grade Accounting students. Research instruments included observation sheets on learning activities, achievement tests, and interviews with teachers and students. The findings indicated a significant improvement in students' learning activities, progressing from a "fairly active" category in the first cycle to a "highly active" category in the third cycle. Learning outcomes also showed consistent growth, with mastery levels increasing from 56.25% in the first cycle, 75% in the second cycle, and 90.62% in the third cycle, accompanied by higher average scores. The FRAC media facilitated students' understanding of financial ratio analysis in a simpler, visual, and interactive way, which enhanced their motivation and engagement in learning. It can be concluded that the FRAC Smart Card is effective in improving students' learning activities and outcomes in Accounting subjects. This study recommends that teachers adopt and develop similar media as an instructional innovation, and that future research should examine its effectiveness across different contexts and subjects.